2018
DOI: 10.1002/pc.24707
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing interfacial and mechanical strength of styrene‐butadiene rubber composites via in situ fabricated halloysite nanotubes/silica nano hybrid

Abstract: In situ fabricated nano hybrid halloysite nanotubes (HNTs‐g‐Silica) by chemically grafting silica nanoparticles onto HNTs was used as the reinforcing filler for styrene butadiene rubber (SBR). The dispersion of HNTs‐g‐Silica and the interfacial interaction between HNTs‐g‐Silica and SBR were systematically investigated. The results suggested that HNTs‐g‐Silica was uniformly dispersed in SBR matrix. Moreover, compared with HNTs or the mixture of mixed HNTs/silica, HNTs‐g‐Silica could immobilize more rubber chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…[49,50] Tan δ at 0 C is corresponding to the wet skid resistance, while tan δ at 60 C reflects the rolling resistance of tire tread rubber, and the rolling resistance will be reduced if the tan δ at 60 C has a lower value. [49][50][51] How to improve the wet skid resistance and reduce the rolling resistance of tire tread rubber at the same time has always been the focus of tire industry. It could be found from the figure that, C 3 N 4 /SiO 2 -SSBR/BR nanocomposites have better comprehensive dynamic properties than SiO 2 -SSBR/BR especially wet skid resistance and rolling resistance, 5% C 3 N 4 / SiO 2 -SSBR/BR nanocomposites in particular (with an increase tan δ of 10.8% at 0 C, and a decrease of 50.5% at 60 C).…”
Section: Dynamic Mechanical Properties Of Ssbr/br Nanocompositesmentioning
confidence: 99%
“…[49,50] Tan δ at 0 C is corresponding to the wet skid resistance, while tan δ at 60 C reflects the rolling resistance of tire tread rubber, and the rolling resistance will be reduced if the tan δ at 60 C has a lower value. [49][50][51] How to improve the wet skid resistance and reduce the rolling resistance of tire tread rubber at the same time has always been the focus of tire industry. It could be found from the figure that, C 3 N 4 /SiO 2 -SSBR/BR nanocomposites have better comprehensive dynamic properties than SiO 2 -SSBR/BR especially wet skid resistance and rolling resistance, 5% C 3 N 4 / SiO 2 -SSBR/BR nanocomposites in particular (with an increase tan δ of 10.8% at 0 C, and a decrease of 50.5% at 60 C).…”
Section: Dynamic Mechanical Properties Of Ssbr/br Nanocompositesmentioning
confidence: 99%
“…The polymers that used to composite with HNTs include polyolefins, epoxy resins, polyamides, natural rubbers, styrene-butadiene rubbers, EPDM rubber, and so on. [24][25][26][27][28] The results showed that halloysite nanotubes contribute to the thermal stability, flameretardant, mechanical, and electrical properties of polymers. Reyhaneh Berahman 5 introduced hexamethylenetetraminemodified halloysite nanotubes into a silicone rubber matrix with different hardnesses, resulting in improved tensile strength and modulus of silicone rubber at a low filler loading.…”
Section: Introductionmentioning
confidence: 99%
“…HNTs have been used as a functional nanofiller to prepare a variety of polymer composites with excellent properties due to their chemically different internal and external surfaces. The polymers that used to composite with HNTs include polyolefins, epoxy resins, polyamides, natural rubbers, styrene‐butadiene rubbers, EPDM rubber, and so on 24–28 . The results showed that halloysite nanotubes contribute to the thermal stability, flame‐retardant, mechanical, and electrical properties of polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation